EFFECT OF IJARAH REVENUE, MUDHARABAH FINANCING AND THIRD-PARTY FUNDS ON THE PROFITABILITY OF ISLAMIC COMMERCIAL BANKS - Ali Nafi’ Addawami; R. Mohd. Zamzami (Transpublika Publisher, 2022)
This research aims to analyze and empirically test the influence of ijarah revenue, mudharabah financing and third-party funds to the profitability of ROA of Islamic Commercial Bank contained in the Financial Services Authority for the 2016-2020 period. The research method used is a quantitative research method because this study uses numbers with statistical calculations and aims to test the hypotheses that have been made. The independent variables in this study were ijarah revenue, mudharabah financing and third-party funds while the dependent variable in this study was profitability (ROA). The research population is Islamic banking registered with the Financial Services Authority (OJK) in 2016-2020, with sample selection using purposive sampling techniques. Therefore, data on the monthly financial statements of Islamic Commercial Banks were obtained which were summarized in the Islamic Banking Statistics for the period 2016-2020, so that 60 research samples were obtained. Data collection techniques in this research use documentation and literature studies. The data analysis techniques used in this study are descriptive statistics, multiple regression analysis, classical assumption tests, determination coefficient tests and hypothesis testing using the EViews 12 analysis tool. Test F results show that ijarah revenue, mudharabah financing and third-party funds simultaneously have a significant effect on profitability (ROA). Meanwhile, T test reveals that ijarah revenue partially had a positive and significant effect on profitability (ROA), while mudharabah financing partially had a negative and significant effect on profitability (ROA) and third-party funds partially had a positive and significant effect on profitability (ROA).